P390 Efficacy and safety of mesenchymal stem cell therapy with darvadstrocel for complex perianal fistulizing Crohn′s disease: multicentric experience in the Basque Country and Navarre. (21st January 2022) - Elorza, A; Arzallus, T; Izagirre, A; Vicuña, M; Rodriguez, C; Cabriada, J L; Rodriguez-Lago, I
Abstract: Background: Perianal fistulizing Crohn′s disease has a negative impact on patients′quality of life and despite advances in medical and surgical treatment, high rates of recurrence are still reported. Mesenchymal stem cell therapy has recently been authorized for the treatment of complex perianal fistulas in adult patients with Crohn's disease, and it may be an effective and safe alternative. The aim of this study was to evaluate the results of efficacy, defined as combined clinical and radiological remission, and safety after administration of darvadstrocel. Methods: A retrospective and observational analysis of patients with complex perianal disease treated with darvadstrocel at three centers in Spain were included. The inclusion criteria and the surgical technique followed the specifications from the Ministry of Health and Consumption. Follow-up visits were performed at, 6 and, 12 months after the treatment and evaluated by clinical disease activity and pelvis magnetic resonance. Results: From November, 2020 to July, 2021, 13 patients (mean age, 39 years, IQR, 30–48, 69% males) were treated with mesenchymal stem cell therapy. The most common type of fistulas were transsphinteric (77%), high intersphinteric (15%) and the suprasphinteric (15%), the latter associated with other types of fistulas. All patients received concomitant anti-TNF (61%), ustekinumab (31%) or vedolizumab (8%). Eight patients (62%) have reached the, 6-month follow-up, five (62%) of them have had combined response, one patient (13%) had radiologic response and two (25%) showed disease progression (Figure, 1). Among those patients with <6 months follow-up, four (80%) of them have shown clinical response. Most of the patients (77%) had no adverse events related to therapy. One patient had rectal bleeding and two patients developed a new fistula or abscess, with no need for reintervention in any of them. Conclusion: The initial experience with mesenchymal stem cell therapy show promising results in terms of effectiveness and safety in the short term in complex perianal disease. A longer follow-up period is still needed to confirm these promising data.